1963
DOI: 10.1029/jz068i003p00919
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic sounds: Investigation and analysis

Abstract: Volcanic sounds were tape‐recorded on ten occasions during the decade 1950–1960. Analyses of the recordings show that underwater sounds from Bárcena volcano in the north‐eastern Pacific, in November 1952, possessed frequencies in a strong harmonic progression with an apparent fundamental frequency of about 50 cps, little energy above 550 cps, and a pulse duration of 1 to 2 sec. Airborne sounds of explosions in Mihara Yama, O Shima volcano, Japan, in January 1954 had an apparent fundamental frequency of 16 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…each have characteristic acoustic signals as well, as first documented by Richards (1963). In this section we describe the typical infrasound signals associated with the predominant types of volcanic activity, as well as the models used to explain them.…”
Section: Hawaiian To Plinian Infrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…each have characteristic acoustic signals as well, as first documented by Richards (1963). In this section we describe the typical infrasound signals associated with the predominant types of volcanic activity, as well as the models used to explain them.…”
Section: Hawaiian To Plinian Infrasoundmentioning
confidence: 99%
“…The first tape recordings of volcanic sounds were apparently made by the NHK Broadcasting Bureau of Japan (Snodgrass and Richards, 1956). In 1952, a program of volcanic acoustics was initiated by James Snodgrass at the Scripps Institution of Oceanography, leading to a decade's worth of underwater and airborne acoustic recordings of volcanic sounds (Richards, 1963), however, the sonobuoy-based recording systems had a poor frequency response below 50 Hz. Richards (1963) provided a table summarizing the results of their investigations, which describes acoustic signals recorded from various idealized styles of volcanic activity.…”
Section: Brief History Of Volcano Infrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…11) prompted researchers to investigate the possibility of a common link between the two phenomena. Even though it has been well known that volcanic eruptions can generate pressure disturbances in the atmosphere with a frequency that can range between 10 33 and 20 Hz (Richards, 1963), until recently there was no systematic recording of temporal variations of these signals near erupting volcanoes. Nowadays the installation of very sensitive microphones that record air-pressure waves with high resolution is an important supplement to the seismic monitoring of active volcanoes (Stromboli-Ripepe et al, 1996 ; Pavlof-Garce ¤s and Hansen, 1998; ArenalGarce ¤s et al, 1998; Sakurajima-Garce ¤s et al, 1999 ; Karimsky/Sangay-Johnson and Lees, 2000; Mt.…”
Section: Visual and Acoustic Observations Related To Tremor Activitymentioning
confidence: 99%
“…Wilcox reported 1 1 distinct sounds associated with activity at Paricutin including a deep throaty roar resulting from the rush of vapours at a small vent and a low growl from intermittent emission of a similar vent (Foshag & Gonzalez 1956, p. 363-364). Richards (1963) studied airborne and submarine noise from 10 volcanic events and found that the characteristics of recorded sounds were related to the type of volcanic activity producing them. For example he found that Hawaiian-type eruptions tend to be acoustically quiet, strombolian activity is characterized by broad-band noise with a moderately well-developed fundamental frequency and harmonics of small intensity, and vulcanian eruptions by a marked peak fundamental frequency and very well-developed harmonics.…”
Section: Introductionmentioning
confidence: 99%